2012
DOI: 10.7318/kjfc/2012.27.3.240
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Consumption of Coffee Beverages and Energy Contribution Ratios of Coffee Beverages and Accompanying Snacks by College Students in Daejeon City and Chungnam Province in Korea

Abstract: This study was performed to investigate the consumption of coffee beverages and energy contribution ratios of coffee beverages and accompanying snacks by college students in Deajeon City and Chungnam Province in Korea. Questionnaire survey, dietary survey, and snack survey using food record method during 3-days were carried out. As a result, we found that 86.9% of male students and 75.6% of female students consumed coffee beverages usually, with no differences between the two groups. However, the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Others have also reported a frequent consumption of coffee among young people with some gender differences [29,30]. A review regarding caffeine consumption concluded that, for the healthy adult population, moderate daily caffeine intake at a dose level up to 400 mg/day is not associated with adverse effects [31].…”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported a frequent consumption of coffee among young people with some gender differences [29,30]. A review regarding caffeine consumption concluded that, for the healthy adult population, moderate daily caffeine intake at a dose level up to 400 mg/day is not associated with adverse effects [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study sample demonstrated a moderate coffee consumption (2-3 times per day) overall, with no big differences in consumption between genders (0.07), with more women though being in the lowest category (few times/year/never). Others have also reported a frequent consumption of coffee among young people with some gender differences [ 29 , 30 ]. A review regarding caffeine consumption concluded that, for the healthy adult population, moderate daily caffeine intake at a dose level up to 400 mg/day is not associated with adverse effects [ 31 ].…”
Section: Discussionmentioning
confidence: 99%